THE EFFECT OF BAD HUMAN ACTIVITIES ON MARINE LIFE AS PORTRAYED IN SAMMY’S ADVENTURE: THE SECRET PASSAGE - LATHIFAH, ISNA NUR (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: ecocriticism, bad humans activities, marine life, Sammy’s Adventure: the Secret Passage movie. The balance of marine life is often damaged by irresponsible humans who do not care about their environment. This problem has inspired some works to criticize humans’ reckless behavior toward environment, especially ocean. Sammy’s Adventure: the Secret Passage is one of the examples that have been created to criticize the bad human activities in the ocean.  This research applies ecocriticism as an approach that is used to find the effect of bad humans activities on marine life described in Sammy’s Adventure: the Secret Passage. The research also applies mise en scene to support the analysis in this movie. In this case, ecocriticism is connected with marine life because ocean is an important part of environment that can be evaluated by using ecocriticism. The result of the study reveals that many problems in marine life are caused by humans. In Sammy’s Adventure: the Secret Passage, Sammy, a turtle, as the main character faces and sees several events which show humans negative activities giving harm for the ocean’s animals and plants. There are three points of bad humans activities on marine life found in this movie, they are marine pollution activity, destructive fishing activity and animal exploitation activity. The effects are not only making the ocean look dirty but also making the aquatic plants unhealthy, preventing them to grow normally or die. Furthermore, the clear effect is felt directly by marine animals. It influences their survival and makes them stressed or often dies. The death of many animals and aquatic plants can decrease the number of population and bring them to the scarcity. It is suggested for researchers to do further research in analyzing problems of marine life in different movie by using same approach.